8 - Intellectuels africains, patriotisme et panafricanisme : à propos de la fuite des cerveaux - Mbonda, Ernest-Marie Mbonda (Africa Development, 2021)
Under the guise of a simple sociological description, the concept of brain drain hides a value judgement on the duties of intellectuals towards their homelands. We would not talk about ‘drain’ if every intellectual was not primarily considered as attached to a specific country, a specific continent, and as having some ‘patriotic duty’ to contribute, with all his/her intellectual capacity, to the develop- ment, prosperity and influence of their homeland. The intellectuals who have chosen emigration could be accused of prioritizing their interests, and shamefully dissociating themselves from the destiny of their countries, their continents and their peoples. Those intellectuals could be blamed for having failed to make a contribution, however modest it could be, to the construction of fair, democratic and prosperous African societies and to help in the implementation of those nationalist and pan-Africanist projects that were envisioned around the early post-independence period. Yet, is patriotism (as well as nationalism) to be consid- ered as a virtue, and should brain drain be regarded as a vice? Aren’t there situa- tions where brain drain itself could be regarded as a virtue, at least in the sense that it could help to put at the service of humankind and its own society (through states that recognize and value it) talents that otherwise would have been left untapped? These are some of the questions, which in fact implicitly contain our assumption, guiding the reflection that we have developed in this article.